Investigating relationship between water production and interfacial activity of γ-oryzanol, ethyl ferulate, and ferulic acid during peroxidation of bulk oil - Mohamad Reza Toorani (Nature Portfolio, 2021)
Abstract In this study, lecithin (as a surfactant) was added to promote the inhibitory-mechanism of γ-oryzanol, ethyl-ferulate and ferulic acid (based on the interfacial phenomena) so as to inhibit the oxidation of stripped sunflower oil. Monitoring the amount of water production as a byproduct of oxidation showed that the water content of the lipid system increased remarkably through the oxidation progress. Lecithin enhanced the critical concentration of hydroperoxides in reverse micelles, compared to the basic state (14.8 vs. 9.2 mM), thereby improving the hydrogen-donating mechanism of antioxidants. The size of reverse micelles increased progressively during the oxidation, while two breakpoints were pointed out in the micelles growth, i.e. at the end of the initiation and the propagation phases. Based on the kinetic data, ferulic acid showed the highest antioxidant activity (23.4), compared to ethyl-ferulate (15.5) and γ-oryzanol (13.7). Generally, lecithin enhanced antioxidant activity (~ 65%) by improving the interfacial performance of antioxidants.